The libation bearers - Hall, Peter; Aeschylus, Choephori (Films for the Humanities and Sciences, 1983)
The play opens as Orestes, Agamemnon's son returns from exile with his friend Phylades and dedicatesb a lock of his hair on his mother Agamemnon's tomb. His sister, Electra and the chorus of trojan women come to offer libations at the tomb, and in a deeply moving scence, brother and sister recognize one another. They swear to avenge their father's death,a s they have been directed to do by Apollo. Disguised as strangers, Orestes and Pylades enter Agamemnon's palace and kill Aegisthus and Clytemnestra. Threatened by furies, he flees to seek Apollo's help.